Mechanical performance optimization of similar thin AA 7075‐T6 sheets produced by refill friction stir spot welding. Issue 6 (12th June 2020) - Yamin, M.F.; Awang, M.; Suhuddin, U.F.H.; Sallih, N.; Klusemann, B.; dos Santos, J.F.
Abstract: Refill friction stir spot welding was applied to weld similar thin AA 7075‐T6 aluminum alloy sheets in a spot‐like joint configuration without a keyhole. The welds were produced using a small tool consisting of sleeve and probe with diameters of 6 mm and 4 mm, respectively. Design of experiment was employed to optimize the welding parameters in terms of the cross tensile strength by using Box Behnken Design. Based on analysis of variance, it can be concluded that plunge depth strongly affects the mechanical performance of the weld. Optimal welding parameters in terms of rotational speed, plunge depth and speed are identified to reach a cross tensile strength of up to 660 N. Abstract : Refill friction stir spot welding (refill FSSW) has been introduced to weld similar thin AA 7075‐T6 using small diameter of tool. The box Behnken design and analysis of variance were employed to optimize the welding parameters. A regression model for the cross tensile strength prediction was developed and has a good agreement with the experimental results. Furthermore, the results showed that plunge depth strongly affects the mechanical performance of the welds.